Skenario Perbaikan Keandalan Pembangkit dengan Peramalan Beban Pada PLTU Anggrek Gorontalo - Yuniahastuti, Irna Tri; Adi Kusuma, Yudha (Engineering Faculty at Universitas Singaperbangsa Karawang, 2023)
The calculation of constraints at the Gorontalo 2x25 MW Orchid PLTU plant obtained a LOLP value of 37.84 days per year. This value is still above the reliability value of PLN standards. This is because in Unit 2, there were POs (Planned Outages) and MOs (Maintenance Outages) in June-July 2021, which were in the form of a first-year inspection in July. The FOR (Force Outage Rate) value is calculated based on disturbance data from plants in 2021. So a scenario was carried out for reliability improvements in the plant. From scenario 1, a reliability value of 36.86 was obtained, and scenario 2 obtained 16.16 days per year; scenario 3 had a value of 1.54 days per year.